Revision of The Code of Canon Law on the Basis of Preambles in the Normative Documents of Pope Francis - Gałkowski, Tomasz (Prawo Kanoniczne, 2026)
The subject of the analyses undertaken is the legislative activity of Pope Francis. A lot of attention has already been devoted to it in various studies analyzing and explaining particular normative solutions, as well as formulating critical comments relating to legislative technique. Another proposal aimed at understanding Francis’ intentions is to look at his legislative activity through the prism of the preambles of individual legislative documents. They contain the ratio legis of the changes being made, which is framed in terms that are broader than merely limited to indicating the purpose of the new legal formulations. The broader ratio legis indicates: 1) the authorization of the legislator to issue the act; 2) the socio-cultural basis; 3) an explanation of the application of the act in the future.